EFEKTIVITAS 6-FURFURYL AMINO PURINE (KINETIN) DAN 6-BENZYLAMINO PURINE (BAP) PADA MEDIA MS TERHADAP PERTUMBUHAN EKSPLAN PUCUK MAHONI (SWIETENIA MAHAGONI) SECARA IN VITRO - DWI TUKAWA, NURICHA Dwi; Wahyono, Rahmad (Universitas Negeri Surabaya, 2013)
Mahogany (Swietenia mahagoni) is among wood plants having economic value, the lack of teak supply has motivated the expansion of mahoni plantation. To support the availability of plant material, propagation by tissue culture technique being a good alternative for mass production. This research was aimed at studying the responsses of shoot induction and callus of top shoot of mahoni as result of effect of type of growth regulators, which is BAP and kinetin at MS medium through in vitro method. The study was conducted in the Laboratory Tissue Culture Nursery Permanent (KBP) Department of Agriculture and Forestry Lamongan, with BAP 1 ppm and kinetin 1 ppm on MS medium for callus growth and bud from the shoot explants mahonis. Results showed that the growth responsse of explants shoot end mahoni into callus and shoots.The percentage of exsplants growth on this test-driving is 26,69%, one that consisting of the percentage of callus growth is 3,5%, and the percentage growth of shoots is 12,75%.